ผลของการซื้อขายในตลาดสินค้าเกษตรล่วงหน้าต่อราคาสินค้าเกษตรไทย กรณีศึกษา: ข้าวขาว 5% - พิชญมหุตม์ ณชภัทร (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อ 1) ศึกษาองค์ประกอบการทำงานของตลาดสินค้าเกษตรล่วงหน้าแห่งประเทศไทย (AFET) 2) ศึกษาการผลิต การตลาด การกำหนดราคาส่งออกและราคาในประเทศของข้าวขาว 5% และเปรียบเทียบ ราคาข้าวขาว 5% ณ ตลาดกรุงเทพฯ ของไทยทั้งก่อนและหลังการซื้อขายในตลาดสินค้าเกษตรล่วงหน้า และ 3) ศึกษา ความสัมพันธ์และอิทธิพลของปัจจัยที่มีผลต่อการกำหนดราคาข้าวขาว 5% ณ ตลาดกรุงเทพฯ ทำการวิเคราะห์เชิงพรรณนา และเชิงปริมาณ โดยใช้ข้อมูลทุติยภูมิรายเดือน 2 ช่วงเวลา คือ ก่อน (ตั้งแต่ มกราคม ปี พ.ศ. 2540 ถึง สิงหาคม ปี พ.ศ. 2547) และหลังมีตลาดล่วงหน้า (ตั้งแต่ กันยายน ปี พ.ศ. 2547 ถึง ธันวาคม ปี พ.ศ. 2555) วิธีการวิเคราะห์ ได้แก่ Independent Samples Test, ค่าสัมประสิทธิ์สหสัมพันธ์เพียร์สัน, ADF test เพื่อทดสอบความนิ่งของข้อมูล, การวิเคราะห์การถดถอย พหุคูณ และพิจารณาค่า t-test, F-test, R2 และ D.W. ที่ระดับนัยสำคัญทางสถิติ 0.05 ผลการวิจัยครั้งนี้ พบว่า 1) องค์ประกอบของตลาดสินค้าเกษตรล่วงหน้า ได้แก่ คณะกรรมการบริหารตลาด ผู้ซื้อขายสัญญาสินค้าเกษตรล่วงหน้า นักเก็งกำไร บริษัทนายหน้า และสำนักหักบัญชี หลังจากที่มีตลาดสินค้าเกษตร ล่วงหน้าเกษตรกร โรงสี และผู้ส่งออก สามารถใช้ราคาในตลาดล่วงหน้าเป็นราคาอ้างอิงเพื่อลดความเสี่ยงและใช้ค้นหาราคา ในอนาคตเพื่อเก็งกำไร 2) เกษตรกรเพิ่มพื้นที่เพาะปลูกข้าวเพื่อหวังราคาหน้าฟาร์มที่เพิ่มสูง ขึ้นจากโครงการรับจำนำข้าวของ รัฐบาล ผู้ส่งออกจะเป็นผู้เชื่อมโยงและส่งผ่านราคาข้าวในตลาดโลกกับราคาข้าวของตลาดส่งออกและตลาดภายในประเทศ โรงสีจะอาศัยราคาจากนายหน้า พ่อค้าขายส่งในตลาดกรุงเทพฯ และพ่อค้าในตลาดส่งออกมาเป็นข้อมูลเพื่อกำหนดราคา อ้างอิงในการรับซื้อข้าวจากเกษตรกร ผลของการซื้อขายสัญญาซื้อขายข้าวขาว 5% ในตลาดล่วงหน้าทำให้ราคาข้าวขาว 5% เฉลี่ย ณ ตลาดกรุงเทพฯ หลังมีตลาดล่วงหน้าสูงขึ้นเมื่อเเทียบกับก่อนมีตลาดล่วงหน้า อย่างมีนัยสำคัญทางสถิติ 0.01 และ 3) หลังมีตลาดล่วงหน้าตัวแปรอิสระมีความสัมพันธ์และมีอิทธิพลต่อตัวแปรตามในระดับสูง ยกเว้นปริมาณ ผลผลิตข้าวเปลือก โดยทุกข้อมูลมีความนิ่งที่ระดับ first integration, I (1) ผลการวิเคราะห์การถดถอยพหุคูณ ได้สมการ 2 รูปแบบ ดังนี้ (1) WPt = 936.12 + 0.08 WRF5t - 0.31 CPt ** + 1.72 FPt ** + 0.11 F.O.B.t-1 * - 0.000129 Qt-10; R2 = 0.9607, D.W. = 2.01 (2) logWPt = 1.55 + 0.12logWRF5t -0.14logCPt **+0.79logFPt **+0.14logF.O.B.t-1 *- 0.01logQt-10; R2 = 0.9617, D.W. = 2.12 ราคาหน้าฟาร์มในปัจจุบันส่งผลต่อราคาข้าวขาว 5% ณ ตลาดกรุงเทพฯในปัจจุบันมากที่สุดคือ ร้อยละ 0.79 อย่างมีนัยสำคัญ ทางสถิติ 0.01 รองลงมาคือราคารับจำนำข้าวเปลือกในปัจจุบันของรัฐบาล และราคาส่งออกในเดือนที่แล้วส่งผลเท่ากันคือ ร้อยละ 0.14 อย่างมีนัยสำคัญทางสถิติ 0.01 และ 0.05 ตามลำดับ จึงกล่าวได้ว่า ณ เวลาปัจจุบัน ราคารับจำนำข้าวเปลือกของ รัฐบาลส่งผลต่อราคาขายส่งข้าวขาว 5% มากกว่าราคาซื้อขายในตลาดล่วงหน้า รัฐบาลจึงยังคงให้ความสำคัญต่อนโยบาย แทรกแซงราคาข้าวในฤดูเก็บเกี่ยว EFFECTS OF TRADING IN AGRICULTURAL COMMODITY FUTURE EXCHANGE ON AGRICULTURAL PRICE IN THAILAND: A CASE STUDY OF WHITE RICE 5% Nachapat Pichayamahoot Faculty of Business Administration and Information Technology, Rajamangala University of Technology Tawan-Ok Chakrabongse Bhuvanarth Campus, Bangkok 10400, Thailand The objectives of this research were 1) to study the functional elements of Agricultural Future Exchange in Thailand (AFET), 2) to study production, marketing and pricing of export and domestic White Rice 5% price and to compare the White Rice 5% price at Bangkok market both before and after the rise of trading in AFET, and 3) to study the relationship and the influence of factors that affected the White Rice 5% pricing at the market. The data was collected by descriptive analysis and quantitative analysis, used monthly secondary data in 2 periods: before (January, 1997 to August, 2004) and after the beginning of trading in AFET (September, 2004 to December, 2012). The methods used to analyze data were Independence Samples Test, coefficient of Pearson Correlation, the test of stationary by ADF test, and Multiple Regression Analysis. The value of t-test, F-test, R2 and D.W. were considered at significance level of 0.05. The results revealed that 1) the functional elements of AFET were board of marketing management, traders, speculators, brokers and the clearing house. After the beginning of trading in AFET, farmers, mills and exporters can reduce their risk and find future price to speculate. 2) The farmers increased their rice production to hope the rising of the price of paddy mortgage’s government. The exporters will integrate the world rice price for the export and domestic markets. The mills will apply the rice price from brokers, wholesale dealer and exporters to define the reference price to buy farmer’s rice. The effect of White Rice 5%’s contracts trading in AFET, the average price of White Rice 5% at the market was higher than before the rise of trading in AFET at significance level of 0.01. 3) The high relationship and the influence of factors that affected the White Rice 5% pricing at the market, excepted quantity of rice. Every data were stationary at first integration level, I(1). The results of Multiple Regression Analysis were 2 equations as follows: (1) WPt = 936.12 + 0.08 WRF5t - 0.31 CPt ** + 1.72 FPt ** + 0.11 F.O.B.t-1 * - 0.000129 Qt-10; R2 = 0.9607, D.W. = 2.01 (2) logWPt = 1.55 + 0.12logWRF5t -0.14logCPt **+0.79logFPt **+0.14logF.O.B.t-1 *- 0.01logQt-10; R2 = 0.9617, D.W. = 2.12 The present farm price was most affected the White Rice 5% pricing at the market today at 0.79 percent at significance level of 0.01, followed by the present price of paddy mortgage’s government and the previous month of export price (F.O.B.), both at 0.14 percent at significance level of 0.01 and 0.05. The present price of paddy mortgage’s government was more affected than the present White Rice 5% price in AFET, and important in the rice harvest season.